2023
DOI: 10.30574/wjarr.2023.17.1.0133
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the relationship between profile factors and locus of control of selected college students in Camarines Norte, Philippines

Abstract: Numerous studies have revealed that locus of control is among the significant factors that contributed to the mental health challenges faced by individuals during the COVID-19 pandemic. According to the theory on locus of control, it is the degree to which a person feels he has control over events of his life, which can be internal or external. Filipinos have been known to adhere to a fatalistic attitude, which can be construed as a form of external locus of control. This study sought to discover the proportio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…While some studies suggest a mediating role of LOC on university support and entrepreneurial intentions, such as Islam's ( 2019) study, which demonstrated that LOC partially mediated the relationship between university support and entrepreneurial inclinations, it can be argued that LOC might have a moderating role on the variables (university environment and entrepreneurial intentions). Studies (Albert & Dahling, 2016;Fabella & Aler, 2023;Wright & DuCette, 1976) support the idea that locus of control can predict achievement in educational contexts. Their initial analysis indicated that internality was positively associated with achievement in open environments but not in traditional ones.…”
Section: The Moderating Role Of Locmentioning
confidence: 96%
See 1 more Smart Citation
“…While some studies suggest a mediating role of LOC on university support and entrepreneurial intentions, such as Islam's ( 2019) study, which demonstrated that LOC partially mediated the relationship between university support and entrepreneurial inclinations, it can be argued that LOC might have a moderating role on the variables (university environment and entrepreneurial intentions). Studies (Albert & Dahling, 2016;Fabella & Aler, 2023;Wright & DuCette, 1976) support the idea that locus of control can predict achievement in educational contexts. Their initial analysis indicated that internality was positively associated with achievement in open environments but not in traditional ones.…”
Section: The Moderating Role Of Locmentioning
confidence: 96%
“…Rotter (1966) introduced the concept of locus of control (LOC), describing it as a person's belief in their ability to influence specific events through their personal traits, distinguishing between internal and external types of LOC. This notion of control is crucial as the degree to which individuals perceive themselves to be in control can significantly impact their attitudes and resilience when faced with challenging situations (Fabella & Aler, 2023). Interestingly, individuals who view themselves as being in a position of control are more inclined to engage in entrepreneurial activities (Rotter, 1966).…”
Section: University Environment and Entrepreneurial Activitiesmentioning
confidence: 99%